Integrative dermatology - Norman, Robert A., 1955-; Shenefelt, Philip D.; Rupani, Reena N. (Weil integrative medicine library., 2014)
Skin health has taken center stage for health care practitioners and patients alike. Not only has skin cancer quickly become the number one form of cancer in the United States, with 3.5 million cancers diagnosed in over 2 million patients annually, but concerns about sun protection and healthy aging have dominated both public media and individual patient concerns. As the largest and most visible organ, the skin displays all evidence of health and vitality, both real and perceived, thereby conferring a tremendous amount of psychological burden on those afflicted with cutaneous ailments. Clinici.